2021
DOI: 10.1155/2021/6395876
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted versus Laparoscopic Partial Nephrectomy for Giant Sporadic Renal Angiomyolipomas of ≥7 cm: A Propensity Score-Matched Analysis

Abstract: Background. To compare the perioperative and functional outcomes between robot-assisted partial nephrectomy (RAPN) and laparoscopic partial nephrectomy (LPN) for giant sporadic renal angiomyolipomas (AMLs) of ≥7 cm. Materials and Methods. Patients with sporadic renal AMLs of ≥7 cm who underwent RAPN or LPN in the First Affiliated Hospital of Nanchang University between 2015 and 2020 were retrospectively analyzed. Propensity score matching (1 : 1) was performed to adjust for potential baseline confounders. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…A previous clinical comparison study reported [28] that the median WIT of LPN in the treatment of giant AMLs (62 patients with a mean tumor size of 8 cm and a mean renal score of 8) was 22 min, compared with only 17 min in the RAPN group (62 patients with a mean tumor size of 8 cm and a mean renal score of 9). Other similar clinical studies also reported WITs that were generally shorter than those reported in our study [23] .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A previous clinical comparison study reported [28] that the median WIT of LPN in the treatment of giant AMLs (62 patients with a mean tumor size of 8 cm and a mean renal score of 8) was 22 min, compared with only 17 min in the RAPN group (62 patients with a mean tumor size of 8 cm and a mean renal score of 9). Other similar clinical studies also reported WITs that were generally shorter than those reported in our study [23] .…”
Section: Discussionsupporting
confidence: 67%
“…Even for patients with the same disease that require surgical intervention, the surgical complications and postoperative outcomes are markedly different depending on the surgical modality chosen. More studies have reported surgical interventions for AMLs involving RAPN, LPN, selective arterial embolization, laparoscopic aspiration, microwave ablation, radiofrequency ablation, and traditional open surgery; they have also included a variety of patients as study subjects, such as patients with giant, bleeding, and central tumor types, but the conclusions reached vary and need to be veri ed by more studies [2,13,[21][22][23][24] . However, there have been no studies that focus speci cally on central renal angiomyolipomas.…”
Section: Discussionmentioning
confidence: 99%
“…There were 31 studies included in the NMA [9,16,21,30–57]. This comprised of one RCT, four prospective studies and 26 retrospective studies (30 propensity score matching studies).…”
Section: Resultsmentioning
confidence: 99%
“…Publication dates ranged from 2008 to 2021. Study data from the 31 included studies are outlined in Table 1 [9,16,21,30–57]. Risk of bias assessment for the RCT included in this study is outlined in Appendix S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation